Hypertension and its risk factors among pregnant garment workers attending a health centre in Bangladesh - Tayeba Khatun; Arifa Akter; Mahesh Kumar Khanal; Zahid Arefin; Rijwan Bhuiyan (Bangabandhu Sheikh Mujib Medical University Journal)
Background: The burden of hypertension among the pregnant garment workers in Bangladesh is not well known. The aim of this study was to determine the prevalence of hypertension and its associated factors among pregnant garment workers attending a health centre in Narayanganj, Bangladesh.